2011
DOI: 10.1590/s1807-55092011000300002
|View full text |Cite
|
Sign up to set email alerts
|

Tempo de recuperação entre a pesagem e o início das lutas em competições de judô do Estado de São Paulo

Abstract: A perda rápida de peso é altamente prevalente entre atletas de luta. No judô, há um período entre a pesagem e o início da competição no qual atletas podem se recuperar da perda de peso. Apesar desse tempo ser determinante para o desempenho, nenhum estudo avaliou seu padrão de duração. Este estudo objetivou determinar o padrão de duração do tempo entre a pesagem e o início das lutas em competições oficiais de judô. Foram analisados 117 atletas do sexo masculino (classes juvenil, júnior e sênior) durante duas co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
2
0
2
Order By: Relevance
“…In a fact, the recovery time between the weighing and competition is relatively long in many combat sports. In judo, during state competition the interval varied between 2.5 to 5 hour [22] and in taekwondo between 16 to 20 hours [13]. In MMA, although there are no surveys published, it is observed that the intervals are typically between 24 to 48 hours.…”
Section: Discussionmentioning
confidence: 99%
“…In a fact, the recovery time between the weighing and competition is relatively long in many combat sports. In judo, during state competition the interval varied between 2.5 to 5 hour [22] and in taekwondo between 16 to 20 hours [13]. In MMA, although there are no surveys published, it is observed that the intervals are typically between 24 to 48 hours.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning this differentiation, the average number of hours available to competitors in amateur events is usually between 2.5 and 5 h in the same session/day, being considered insufficient time for the replenishment of food and hydration. Although extreme methods may prevent a loss of athletic performance, they may result in an increased tendency to engage in potentially harmful RWL procedures [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Segundo Artioli et al (2011), com 117 atletas de judô das classes juvenil, júnior e sênior, todos do sexo masculino, demostraram que o período médio entre a pesagem e o início das lutas foi de aproximadamente 4 horas, onde a maior parte dos atletas tinham aproximadamente 2,5 -5 horas como tempo de recuperação para o combate.…”
Section: Tempo De Recuperação Do Peso Após a Pesagem Oficialunclassified